The impact of human resource management practices on organizational performance case study: Manufacturing enterprises in Kosovo - Arta Jashari; Enver Kutllovci (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The purpose of this study is to examine the impact of human resource management practices on organizational performance. In this study a total of 100 managers of manufacturing firms in Kosovo from public and private sectors have responded to the survey. The survey questionnaire had contained 39 items covering selected HRM practices and organizational performance. Our empirical results show that managers of manufacturing firms in Kosovo recognize the importance of employees in their organization and apply practices to manage them effectively. The outcome of correlation analysis provides evidence that HRM practices positively and significantly influence organizational performance. Recruitment and selection practices show the strongest positive association with organizational performance (rho = 0.905) compared to other practices. Regarding to our findings we suggest that with a good recruiting and selection, the organization will fill with a group of potentially qualified candidates. Also, companies should continuously train and develop and involve their employees as they are viewed as the most important resources source of competitive advantage.
Keywords: M10; M12; M52; 650; human resources management practices; organizational performance; recruitment; training; reward; participation; Kosovo